KLASIFIKASI GENRE MUSIK DENGAN MENGGUNAKAN METODE MACHINE LEARNING - Sereati, Catherine Olivia; Radix W. C, Hilarius; W Pandjaitan, Lanny; Kartwidjaja, Maria Angela (Website, 2023)
This research discusses how to classify music genres using machine learning.. Music of the same genre usually shares specific characteristics related to instrumentation, rhythmic structure, and musical pitch. Music genres can be done using the Machine Learning method. The Machine Learning algorithms used in this study are K-Nearest Neighbor, Random Forest, and Naïve Bayes. Furthermore, this study will compare the accuracy of the three methods. The primary data used in this study is the result of downloading from the internet. Machine learning programming is used through the Google Colab platform with the Python programming language. From the analysis and testing results, it was found that the Random Forest method has the highest level of accuracy